Results on n-tupled fixed points in complete ordered metric spaces. - Dalal, Sumitra (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
The aim of this paper is to study n-tupled coincidence and n-tupled fixed point results, a new notion propounded by M.Imdad et.al.[13] for compatible maps in partially ordered metric spaces. Our results generalize, extend and improve the coupled fixed point results of Bhaskar and Lakshmikantham, Nonlinear Analysis: Theory, Methods and Applications, vol.65, no.7, 2006, pp. 1379-1393, V. Lakshmikantham and L. Ciric, Nonlinear Analysis, Theory, Method and Applications, vol. 70, no12, 2009, pp. 4341-4349, tripled fixed point theorems by Berinde and Borcut, Nonlinear Analysis, Volume 74, Issue 15, October 2011, Pages 4889-4897, Quadruple fixed point theorems by E. KarapÄ±nar and V. Berinde, Banach Journal of Mathematical Analysis, vol. 6, no. 1, pp. 74 89, 2012 and multidimensional fixed point results by Muzeyyen Erturk and Vatan Karakaya, Journal of Inequalities and Applications 2013, 2013:196, pp. 1-19, M. Imdad, A. H. Soliman, B. S. Choudhary and P. Das, Journal of Operators, Volume 2013, Article ID 532867, pp. 1-8 and M. Paknazar, M. E. Gordji, M. D. L. Sen and S. M. Vaezpour, Fixed Point Theory and Applications 2013, 2013:11 etc.